O pastor como gestor? chances e desafios da administração e da gestão no meio da Igreja Presbiteriana do Brasil - Souza, Timóteo Freitas de (2010)
This dissertation aims at presenting management models for religious organizations, having as its object of analysis the Presbyterian Church in Brazil. The goal is to identify the challenges and what chances management and administration theories have to be approved upon these contexts. The first part will deal with the management theories from the thinking of Peter Drucker, especially emphasizing the need for changes and innovations in the midst of nonprofit organizations. The amauterism by which management processes are conducted in churches is emphasized as the main problem of religious organizations. The second part presents the basic framework of the Presbyterian Church government system in Brazil from the perspective of a Reformed Calvinist thinking approach and also from what recommends the Constitution of the Presbyterian Church in Brazil. Finally, there is a description and analysis of the IPB praxis, followed by a summarized presentation of the ecclesiastic management disciplines programs on Presbyterian Church theological courses.